Adsorption Capacity of Activated Charcoal Made of Rice Husk on Cd(II) Metal Ions - Eka Widyasari; Supriadi Supriadi; Irwan Said (Universitas Tadulako, 2021)
Rice husk is one of the by-products of the rice milling process that can be used as activated charcoal to adsorb metal ions. This study aimed to determine the optimum pH and adsorption capacity of Cd(II) ions by activated charcoal made of rice husk using the Atomic Absorption Spectrophotometry (AAS) method. Determination of the optimum pH adsorption of activated charcoal was carried out by varying the pH of 2, 3, 4, 5, 6, 7, and 8. Based on the analysis results of the optimum pH for metal adsorption, pH 7 with percent absorbed metal 99.94%, while adsorption of Cd(II) ions using activated charcoal was carried out with several variations of concentration to study adsorption isotherm. The adsorption isotherm model of activated charcoal adsorption followed the Langmuir isotherm model. The results of this analysis obtained that the maximum adsorption capacity (qmax) of Cd(II) ions were 2.068 mg Cd/g.